Temperature‐Dependent Characteristics of AlGaN/GaN Nanowire Channel High Electron Mobility Transistors. Issue 16 (23rd June 2019) - He, Yunlong; Huang, Zeyang; Zhang, Meng; Wu, Mei; Mi, Minhan; Wang, Chong; Yang, Ling; Zhang, Chunfu; Guo, Lixin; Ma, Xiaohua; Hao, Yue
Abstract : In this work, three AlGaN/GaN nanowire channel high electron mobility transistors (NC‐HEMTs) with different channel widths have been fabricated. The temperature dependent characteristics of NC‐HEMTs are studied and compared with conventional HEMT. The results show that the on‐state current density of NC‐HEMTs have weaker temperature dependence, and the threshold voltage variation of NC‐HEMTs is lower. In addition, the temperature characteristics of the drain‐induced barrier lowering of NC‐HEMT are first reported. Moreover, there are two main scattering mechanisms that influence the transconductance characteristics of NC‐HEMT, phonon scattering and Coulomb scattering, which correspond to different gate voltage biases. Abstract : Three AlGaN/GaN nanowire channel high electron mobility transistors (NC‐HEMTs) with different channel widths have fabricated, and the temperature‐dependent characteristics are studied and compared with conventional HEMT. The test results of current density, threshold voltage and drain‐induced barrier lowering show that the smaller the channel width is, the better is the temperature stability of NC‐HEMT. Moreover, there are two main scattering mechanisms influencing the transconductance characteristics of NC‐HEMT.